Leveraging Factorial Design for Enhancing Formulation of Ketorolac Tromethamine Fast-Disintegrating Tablets - Chappidi, Suryaprakash Reddy; Mopuri, Deepa (Indian Journal of Pharmaceutical Education and Research)
Aim: Fast disintegrating tablets of Ketorolac tromethamine were prepared by formulating it with various super disintegrants with view to reduce disintegration time of tablets and to increase dissolution properties. Materials and Methods: The study employed One Factor at a Time (OFAT) tests to identify crucial variables and optimal response ranges. The primary factors affecting the disintegration time and drug release were found to be Croscarmellose sodium, Crospovidone, and Magnesium stearate concentrations and these were considered as independent factors, with disintegration time and drug release after 10 min as dependent variables. The experimental design and data analysis were performed using Stat-Ease Design Expert® V12.0.1.0. Results: The study utilized FTIR to analyze pure Ketorolac and its combination with super disintegrants. Pre-compression testing was conducted to assess the flow properties of the powder blend, and all formulations exhibited desirable flow characteristics. All formulations were found to have Average densities between 0.45 g/cm3 and 0.56 g/cm3, a repose angle between 25.5 and 29.6º, compressibility index between 8.69 and 30.35, Hausner’s ratio from 1.09 to 1.43. Tablet formulations had suitable hardness, thickness, disintegration time, and friability. Response polynomial equations were generated to quantify the impact of excipient concentrations on Ketorolac release parameters. Croscarmellose sodium concentration had a direct influence on disintegration time, while Crospovidone and Magnesium Stearate did not affect disintegration time. Conclusion: The study demonstrates that fast-dissolving tablets of Ketorolac tromethamine can be effectively produced using a direct compression method and a range of super disintegrants in various concentrations. The formulation with the highest concentration of Croscarmellose sodium as the super disintegrant yielded the best results in terms of disintegration time and solubility.
Keywords: Ketorolac tromethamine; Croscarmellose sodium; Crospovidone and magnesium stearate; One Factor at a Time approach (OFAT).